2019
DOI: 10.1111/cga.12336
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for abdominal wall defects

Abstract: In the last decades, the prevalence of gastroschisis (GS) has increased worldwide. The purpose of this study was to identify maternal risk factors explaining the described gain and to identify differences between GS and omphalocele (OC). A case‐control design was used to compare GS (n = 36) and OC (n = 18) mothers to control group (CG; n = 30) matched for maternal age. Specialized questionnaires and mothers' prenatal records were used, and participants completed a structured interview. Focus was on medical his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The background for this age-related ARM development is unclear. Advanced paternal age may be ; younger maternal age is known to be associated to congenital defects of the abdominal wall, 12 and therefore a combination of both could increase the risk for congenital malformations like ARM. Contrary to the latest studies, we did not find an increased risk of ARM following sterility treatment, hormone intake or in-vitro fertilization.…”
Section: Evaluation Of Prenatal Risk Factors and Rising Incidencementioning
confidence: 99%
“…The background for this age-related ARM development is unclear. Advanced paternal age may be ; younger maternal age is known to be associated to congenital defects of the abdominal wall, 12 and therefore a combination of both could increase the risk for congenital malformations like ARM. Contrary to the latest studies, we did not find an increased risk of ARM following sterility treatment, hormone intake or in-vitro fertilization.…”
Section: Evaluation Of Prenatal Risk Factors and Rising Incidencementioning
confidence: 99%
“…However, there are only few studies on the effects of maternal medication on the risk of omphalocele. [24][25][26][27] The aim of this study was to assess and identify potential maternal risk factors of omphalocele, and especially to assess the safety and effects of the medications used during the first trimester of pregnancy. We hypothesized that maternal exposures during the first trimester of pregnancy would affect the risk of omphalocele.…”
Section: Introductionmentioning
confidence: 99%
“…46% of the mothers affected by an omphalocele reported alcohol intake in the pregnancy in this cohort [6]. Interestingly, smoking has no statistically significant influence on the incidence of omphalocele [5].…”
Section: Discussionmentioning
confidence: 70%
“…Fetal alcohol spectrum disorders are characterized by specific craniofacial anomalies, neurodevelopmental disorders, growth restriction, and cardiac anomalies, but traditionally not omphalocele. A retrospective observational study of 27,438 births at a German University hospital showed that none of the 18 cases of omphalocele over an 11-year period was associated with maternal alcohol [5]. However in the National Birth Defect Prevention Study undertaken across multiple US centers, the adjusted Odd Ratio between periconceptional maternal alcohol consumption and the 254 cases of chromosomally normal and non-syndromic omphalocele was 1.50 (CI 1.15-1.96).…”
Section: Discussionmentioning
confidence: 99%